Effect of CdO addition on photon, electron, and neutron attenuation properties of boro-tellurite glasses. Issue 5 (1st March 2021) - AlBuriahi, M.S.; Hegazy, H.H.; Alresheedi, Faisal; Olarinoye, I.O.; Algarni, H.; Tekin, H.O.; Saudi, H.A.
Abstract: This research article aims to study the effect of CdO addition on the radiation shielding characteristics of boro-tellurite glasses in the composition of 50B2 O3 - (50-x) TeO2- xCdO, where x = 0, 10, 20, 30, 40 and 50 mol%. These glasses were exposed to gamma radiation and the transmitted gamma photons were evaluated for energies varying from 15 keV to 15 MeV using Geant4 simulation toolkit. The number of transmitted photons was then used to characterize the gamma shielding for the studied glasses in terms of linear/mass attenuation coefficients, MFP, Zeff, and HVL. The simulation outcomes were theoretically confirmed by using Phy-X software. The beta (electron) shielding characterization of the involved glasses was also investigated by determining the projectile range and stopping power using ESTAR software. Additionally, the fast neutron shielding characterization of the glasses was achieved by evaluating removal cross-section (ΣR ). The results reveal that the CdO has a small influence on the shielding performance of the boro-tellurite glasses against gamma, beta, and neutron radiations. The shielding performance of the boro-tellurite glasses was compared with that of common shielding materials in terms of MFP. It can be concluded that the boro-tellurite glasses regardless of the concentration of CdO content have promising shielding performance to be used for radiation applications.